Meropenem-Vaborbactam vs. Piperacillin-Tazobactam in TANGO I (a Phase 3 Randomized, Double-blind Trial): Outcomes by Baseline MIC in Adults with Complicated Urinary Tract Infections or Acute Pyelonephritis. (4th October 2017) - Walsh, Thomas J; Bhowmick, Tanaya; Darouiche, Rabih; Zaitsev, Valerii; Giamarellos-Bourboulis, Evangelos; Shorr, Andrew F; Fedosiuk, Elena; File, Thomas M; Loutit, Jeffrey S; Lomovskaya, Olga; Dudley, Michael N; Perlin, David
Abstract: Background: Meropenem-vaborbactam (M-V) is being developed for gram-negative infections, including complicated urinary tract infections (cUTIs) and multidrug-resistant bacterial infections. TANGO I was a Phase 3, multicenter, double-blind, randomized study of M-V vs. piperacillin-tazobactam (P-T) for treatment of adults with cUTI/acute pyelonephritis (AP). Superiority of M-V over P-T at the FDA primary endpoint has been reported. The effect of baseline MICs of Enterobacteriaceae to both study drugs and by susceptibility vs. non-susceptibility to P-T on clinical/microbiological outcome at end of intravenous treatment (EOIVT) was investigated. Methods: MICs were conducted on baseline urinary isolates using CLSI methods. Susceptibility to P-T was defined as MIC ≤16 µg/mL (FDA/CLSI). Results: Of 550 subjects randomized, 374 (68.0%) were included in m-MITT (165/192 [85.9%] in M-V and 154/182 [84.6%] in P-T groups had baseline Enterobactericeae). Mean duration of IV therapy was 8 days. Clinical outcomes were >90% across all MICs (Table 1). Conclusion: At EOIVT, clinical cure and microbial eradication rates were >90% for both groups with no trend in responses according to baseline study drug MIC. M-V is highly active against Enterobacteriaceae in vitro and in patients, and is a potential new treatment option for cUTI/AP. Disclosures: T. J. Walsh, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant; Astellas: Consultant and Investigator, Consulting fee and Research grant; Allergan: Consultant and Investigator, Consulting fee and Research grant; Merck: Consultant and Investigator, Consulting fee and Research grant; A. F. Shorr, Astellas Pharma Global Development, Inc: Consultant and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; Cidara: Consultant, Consulting fee; Merck: Consultant, Scientific Advisor and Speaker's Bureau, Research support and Speaker honorarium; T. M. File Jr., Allergan: Consultant, Consulting fee; Cempra: Consultant, Consulting fee; The Medicines Company: Consultant, Consulting fee; Merck: Consultant, Consulting fee; MotifBio: Consultant, Consulting fee; Pfizer: Consultant, Consulting fee; Paratek: Consultant, Consulting fee; Nabriva: Investigator, Research grant; J. S. Loutit, The Medicine's Company: Employee and Shareholder, Salary; O. Lomovskaya, The Medicine's Company: Employee and Shareholder, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary